Integration of Environmental Governance with Economic Policy: Towards a Green Governance Model in Makassar City - Sanjaya, Dean Galang; Izzatunnisa, Aulia (Adaptive Governance Research, 2026)
Purpose: This study examines the integration of environmental governance and economic policy toward the development of a green governance model in Makassar amid rapid urbanization and increasing environmental pressures. Subjects and Methods: The study employed a quantitative explanatory approach involving 120 respondents consisting of government officials, environmental stakeholders, academics, and urban development practitioners. Data were collected using structured questionnaires based on a five-point Likert scale and analyzed using descriptive statistics, correlation analysis, classical assumption testing, and multiple linear regression with SPSS. Results: The findings indicate that environmental governance integration in Makassar City was categorized as high, particularly in policy coordination and institutional collaboration. Green governance implementation also demonstrated positive results, especially in sustainability-oriented planning and stakeholder participation. Correlation analysis revealed a strong positive relationship between environmental governance integration and green governance implementation. Regression analysis further confirmed that integrated governance mechanisms significantly influence sustainability-oriented governance practices. The study also identified institutional constraints related to policy coherence, ecological responsiveness, and the tension between economic development priorities and environmental sustainability objectives. Conclusions: The study concludes that environmental governance integration functions as an important foundation for strengthening green governance implementation. Stronger policy coherence, institutional coordination, and administrative capacity remain essential for promoting sustainable urban governance in Makassar City.